2020
DOI: 10.1002/joc.6445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of precipitation datasets against local observations in southwestern Iran

Abstract: This study provides a comprehensive evaluation of a great variety of state-of-theart precipitation datasets against gauge observations over the Karun basin in southwestern Iran. In particular, we consider (a) gauge-interpolated datasets (GPCCv8, CRU TS4.01, PREC/L, and CPC-Unified), (b) multi-source products (PERSIANN-CDR, CHIRPS2.0, MSWEP V2, HydroGFD2.0, and SM2RAIN-CCI), and (c) reanalyses (ERA-Interim, ERA5, CFSR, and JRA-55). The spatiotemporal performance of each product is evaluated against monthly prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 63 publications
3
39
3
Order By: Relevance
“…At present, with its long time-series, good spatiotemporal resolution, and large number of parameters available [99], ERA5 is one of the best and complete global-gridded reanalysis meteorological datasets [34,[100][101][102][103]. However, its derived precipitation is still far from "state-of-the-art" conditions [104][105][106][107]. As a result, our validation implicitly showed that dataset resolution is still insufficient to capture precipitation heterogeneity in small catchments by smoothing flood peaks.…”
Section: Resultsmentioning
confidence: 92%
“…At present, with its long time-series, good spatiotemporal resolution, and large number of parameters available [99], ERA5 is one of the best and complete global-gridded reanalysis meteorological datasets [34,[100][101][102][103]. However, its derived precipitation is still far from "state-of-the-art" conditions [104][105][106][107]. As a result, our validation implicitly showed that dataset resolution is still insufficient to capture precipitation heterogeneity in small catchments by smoothing flood peaks.…”
Section: Resultsmentioning
confidence: 92%
“…There were small changes related to vegetation modelling. For a region with a low density of gauges in Iran, Fallah et al (2020) showed that ERA5 precipitation is closer to local observations than ERA-Interim but that GPCCv8…”
Section: Previous Analysesmentioning
confidence: 80%
“…Diverse results are more common in data sparse regions or in regions where data are not generally available to all data sets. It is therefore difficult to determine which is closer to the truth in a global assessment like this, and more detailed regional studies, such as Fallah et al (2020), are needed.…”
Section: Discussionmentioning
confidence: 99%